Cycling and cardiovascular disease risk factors including body composition, blood lipids and cardiorespiratory fitness analysed as continuous variables: Part 2—systematic review with meta-analysis. Issue 14 (31st May 2019) - Nordengen, Solveig; Andersen, Lars Bo; Solbraa, Ane K; Riiser, Amund
Abstract : Objectives: We aimed to examine the relationship between cycling (particularly commuter cycling) and risk factors associated with cardiovascular diseases (CVDs) including body composition, blood lipids and cardiorespiratory fitness. This study differed from our recent (Part 1) systematic review in that risk factors for CVD were analysed as continuous variables rather than being present or absent. Design: Systematic review and meta-analysis. Eligibility criteria: We searched four databases (Web of Science, MEDLINE, SPORTDiscus and Scopus). All quantitative studies, published until August 2017, were included when a general population was investigated, cycling was assessed either in total or as a transportation mode, and CVD risk factors were reported. Methods: We analysed body composition, physical activity (PA), cardiorespiratory fitness (CRF), blood lipids and blood pressure (BP). Skinfold, waist circumference and body mass index were analysed and prioritised in that order when more than one measure were available. PA included measures of counts per minutes, moderate-to-vigorous PA or minutes per week. CRF included results of maximal tests with or without expired air or submaximal test. For blood lipids and BP, separate analyses were run for low-density and high-density lipoprotein, triglycerides, total cholesterol, systolic BP and diastolic BP. Studies were excluded when reporting dichotomous outcomes or when cycling and walking were combined. Heterogeneity was investigated using I 2 . Results: Fifteen studies were included; the majority reported commuter cycling. In total, we included 5775 cyclists and 39 273 non-cyclists. Cyclists had more favourable risk factor levels in body composition −0.08 (95% CI −0.13 to −0.04), PA 0.13 (95% CI 0.06 to 0.20), CRF 0.28 (95% CI 0.22 to 0.35) and blood lipids compared with non-cyclists. There was no sex difference in risk reduction. Conclusion/implication: Cycling mitigated the risk factor profile for CVD. A strength of this systematic review is that all the risk factors were analysed as continuous variables. These data provide evidence for practitioners, stakeholders, policy-makers and city planners to accommodate and promote cycling. Systematic review registration: PROSPERO CRD42016052421.